Acceptance of e-learning system at private university in Indonesia during the covid-19 pandemic: students' perspectives - Achmad Solichin; Riki Wijaya (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
The Covid-19 pandemic in Indonesia has an impact on changes in policies and the learning process at Budi Luhur University (UBL). The complete online learning policy has been implemented since the 2nd semester of 2019/2020, which began in March 2020. Students and lecturers carry out teaching and learning activities through an e-learning system developed in 2005. Although it has been implemented for a long time, the level of acceptance has never been measured comprehensively. This research has a contribution in measuring the level of acceptance of the e-learning. In addition, before the Covid-19 pandemic, the use of the e-learning system was still partially implemented and only for a few courses. In this study, an analysis of the student acceptance of the UBL e-learning system was carried out by involving respondents and a more comprehensive acceptance model. The modeling used in this study refers to the Comprehensive Technology Acceptance Model (CTAM) with seven exogenous variables and five endogenous variables. Testing and analysis are based on variant-based structural equation models, namely Partial Least Square (PLS) using the SmartPLS application. The results show that nine main factors influence student acceptance of the e-learning system: system quality, content quality, information quality, accessibility, enjoyment, perceived ease of use, perceived usefulness, and student attitudes towards applications and behavioral intention to use. This research is helpful for UBL and other educational institutions as material for developing a quality e-learning system accepted by its users.